2014
DOI: 10.1080/17441692.2014.880501
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality, social capital and service: Factors promoting resilience among Expert Patients living with HIV in Ethiopia

Abstract: People living with HIV (PLHIV) in Ethiopia and other developing nations face numerous challenges to their health and well-being, including poverty, limited healthcare infrastructure, and high levels of societal stigma. Despite these challenges, resilient trajectories have been observed even within such resource-limited settings. In Ethiopia, such resilience is exemplified by the ‘Expert Patients’, HIV-positive lay health workers who function as adherence counsellors, health educators, outreach workers and comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Qualitative studies of resilience among PLWH highlight the limitations of existing quantitative studies and extant measures (Bartone, Ursano, Wright, & Ingraham, 1989;Connor & Davidson, 2003;Wagnild & Young, 1993). Qualitative findings indicate that among PLWH, mastery for management of HIV is important but absent from most resilience measures (Emlet, Tozay, & Raveis, 2011;Hussen et al, 2014;Kaplan et al, 2014;Teti, French, Bonney, & Lightfoot, 2015). Other studies suggest that interpersonal resilience components (e.g., HIV support groups and relationships with healthcare professionals) are important but are excluded from most measures (Emlet et al, 2011;Hussen et al, 2014;Kaplan et al, 2014;Teti et al, 2015), or need further development as evidenced by the limited inclusion of social support specific for PLWH in the reviewed studies (Molassiotis et al, 2002;Sodergard et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Qualitative studies of resilience among PLWH highlight the limitations of existing quantitative studies and extant measures (Bartone, Ursano, Wright, & Ingraham, 1989;Connor & Davidson, 2003;Wagnild & Young, 1993). Qualitative findings indicate that among PLWH, mastery for management of HIV is important but absent from most resilience measures (Emlet, Tozay, & Raveis, 2011;Hussen et al, 2014;Kaplan et al, 2014;Teti, French, Bonney, & Lightfoot, 2015). Other studies suggest that interpersonal resilience components (e.g., HIV support groups and relationships with healthcare professionals) are important but are excluded from most measures (Emlet et al, 2011;Hussen et al, 2014;Kaplan et al, 2014;Teti et al, 2015), or need further development as evidenced by the limited inclusion of social support specific for PLWH in the reviewed studies (Molassiotis et al, 2002;Sodergard et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Qualitative findings indicate that among PLWH, mastery for management of HIV is important but absent from most resilience measures (Emlet, Tozay, & Raveis, 2011;Hussen et al, 2014;Kaplan et al, 2014;Teti, French, Bonney, & Lightfoot, 2015). Other studies suggest that interpersonal resilience components (e.g., HIV support groups and relationships with healthcare professionals) are important but are excluded from most measures (Emlet et al, 2011;Hussen et al, 2014;Kaplan et al, 2014;Teti et al, 2015), or need further development as evidenced by the limited inclusion of social support specific for PLWH in the reviewed studies (Molassiotis et al, 2002;Sodergard et al, 2006). Neighborhood social capital (e.g., availability of clinics that distribute equipment and financial vouchers, and availability of supportive organizations for PLWH) may also be critical to fostering positive adaptation to adversities (Emlet et al, 2011;Hussen et al, 2014;Kaplan et al, 2014;Tariq et al, 2016;Teti et al, 2015), yet these components have been excluded from the most used resilience measures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies based in several sub-Saharan African countries have described how social capital can improve HIV care engagement in very concrete ways. For example, social network contacts can educate one another about HIV, provide transportation assistance to get to appointments, or simply endorse health-promoting norms that make an HIV-positive individual feel better about engaging in care (Hussen et al, 2014;Ware et al, 2009). Second, observational studies in the US are mixed, but largely support the idea of a similarly positive relationship between social capital and HIV-related outcomesincluding HIV symptom management and ART adherence (Phillips et al, 2013;Ransome et al, 2018;Webel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, it can be observed that spirituality has helped PLHIV to cope with HIV (Ironson, Kremer, & Lucette, 2016;Pecoraro et al, 2016). Other studies have indeed shown that spirituality is a resource used to overcome the challenges presented by HIV (Hussen et al, 2014;Szaflarski, 2013). Spirituality in overcoming adverse events could therefore play an important role among persons with HIV infection/AIDS, particularly among heterosexuals.…”
Section: Discussionmentioning
confidence: 99%